Africa's comodity problems : towards a solution - United Nations (Geneva, Switzerland United Nations)
The material contains information by a group of experts on African Commodity Problems established on March 22, 1989.
opc 28/12/16
Loans
Keywords: Commodities; Economic policy; Economic growth; Africa